Poly(n-alkylsilsesquioxane) liquids prepared by cosolvent-free hydrolytic polycondensation of n-alkyltrialkoxysilanes: effects of liquid–liquid phase separation during aging and alkyl chain length on structure and viscosity. Issue 39 (13th September 2016) - Fukuda, Yuko; Kajihara, Koichi; Kakinoki, Shiori; Jang, Junhyeok; Yoshida, Hirohisa; Kanamura, Kiyoshi
Abstract : Trimetoxy- and triethoxysilanes with the same n -alkyl groups yield polysilsesquioxane liquids of similar properties by cosolvent-free hydrolytic polycondensation via aging. Abstract : The effect of the alkyl chain length and alkoxy groups on the viscosity and related properties of polysilsesquioxanes (PSQs) prepared by cosolvent-free hydrolytic polycondensation from n -alkyltrialkoxysilane–water binary systems via aging was investigated. n -Alkyltrialkoxysilanes with ethyl, n -propyl, and n -butyl groups gave PSQ liquids, whereas those with methyl groups yielded gels. The viscosity of the PSQ liquids remained stable over a month at room temperature despite the presence of many SiOH groups, and decreased with an increase in the alkyl chain length. The aging step was crucial for obtaining PSQ liquids with low viscosities, and both n -alkyltrimethoxysilane and n -alkyltriethoxysilane with the same alkyl group produced PSQ liquids with comparable viscosities. However, during aging, liquid–liquid phase separation occurred only in the solutions derived from alkyltrimethoxysilanes. These observations confirmed that liquid–liquid phase separation is not essential for the preparation of PSQ liquids. The temperature dependence of the viscosity indicated that the PSQ liquids are fragile.